MOTIVASI BELAJAR SISWA TERHADAP PEMBELAJARAN DARING:STUDY KASUS DI SISWA KELAS 6 C SD NEGERI 01 BUANTAN LESTARI - Pitaloka, Widuri Bebby; Cahyani, Febriska Dwi; Sumaji, Sumaji; Guslinda, Guslinda; Martini, Martini (Jurnal Manajemen Pendidikan, 2020)
This study aims to explain in detail how the objective conditions of motivation experienced by students in online learning during the Covid-19 pandemic. This study uses a qualitative approach with the observation method. The research was conducted at SDN 01 Buantan Lestari, Bungaraya Subdistrict, Siak Regency, involving 24 students of grade 6 C. The data collection techniques in this study used observation sheets. The data analysis technique used in this study is to calculate the percentage of data from each indicator, then interpret the data presentation score and analyze each indicator in depth. The results of this study indicate that the student's learning motivation is obtained from the percentage score of the motivation which amounts to. This research is expected to be an evaluation of various parties in organizing online learning at SDN 01 Buantan Lestari, especially those involving motivation in it, this research is also expected to be research material for other researchers in analyzing and developing student learning motivation in online learning during emergencies in elementary schools